21 Evaluation of the rapid access chest pain service. (October 2018) - McGovern, L; Madders, G; Kelly, J; Keady, C; McIntyre, E; Hynes, B; Crowley, J
Abstract : Introduction: Rapid Access chest pain clinics (RACPC) provide an important service for the timely assessment of patients with recent onset chest pain of possible cardiac origin. As current guidelines on stable chest pain shift towards the use of non invasive imaging, we sought to critically evaluate our contemporary RACPC as part of plans to develop and improve our service. Methods: We conducted a retrospective review of patients attending the RACPC in University Hospital Galway from 1st January 2016 to the 31st December 2016. Data including baseline demographics, cardiovascular risk factors, subsequent investigations and patient outcomes were collated from patient medical records. European Society Guidelines (ESC) pre test probability scoring system was applied. Results: 640 patients presented to RACPC over the 1 year study period. 56% (n=358) were male with an average age of 55 years. In terms of risk factor profile; 18% (n=118) were current smokers, 64% (n=412) had a family history of CAD, 5% (n=29) were known diabetics, 35% (n=226) had hypertension and 48% (n=305) had dyslipidaemia. Table 1 shows pre test probability calculated by ESC scoring system. Figure 1 above illustrates the investigations conducted in the RACPC. From the total group, 5% (n=31) of patients were referred directly for angiography; 6% (n=41) had other investigations for non chest pain symptoms. The remaining 89% (n=568) underwent exercise treadmill testing (ETT). A total of 389 patients had an ETT and 98% of these were discharged. 116 patients had a positive ETT and 99% of these had a further investigation. 91% of this group (n=106) had invasive angiography and 8% (n=9) had CT angiography. 63 patients had an inconclusive ETT. Ultimately, only 38 patients (22% of all angiograms) had evidence of significant heart disease which required further intervention. All CTCAs performed showed normal coronaries/non-obstructive disease. Interestingly, in the group with a pre test probaility of <15%, 95% (n=76) of patients underwent exercise treadmill test as an initial investigation. Of these, 92% (n=70) were negative. Of the 8% (n=6) that had a positive stress, 1 patient had significant CAD. Ultimately, 99% of this group had a negative test. Conclusion: The chest pain clinic provides a useful pathway for evaluation of low risk chest pain. Most patients were evaluated and discharged to their GP avoiding the need for outpatient or ED review. Exercise treadmill testing remains a useful test to help stratify patients according to risk of CAD however a significant number of patients continue to require invasive angiography. Selective referral of patients with abnormal ETTs for CT angiography may help to reduce this number significantly. In this study group, use of the ESC pretest probability score would potentially reduce the need for any investigation in up to 12% of patients.